Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I don't really know how to explain it as I am not too good at maths vocabulary and mildly good at maths but there is always a question which stumps us and this is mine.

I have two terms, the second(7) and the fourth(43) and the rule which says "the next term in another sequence is to multiply the previous term by 3 and then subtract x, where x is an integer". It wants me to find the first term of this sequence.

I've looked it up on the internet and perhaps I didn't search it right, but all I got was answers to simple sequences which had basic addition to each term with no rules.

Since the answer is needed tomorrow(next-day homework question) and I've tried all resources except this one available to me, I have resorted to this. I ask you, what is the first term and how did you get it? Many thanks in advance.

share|cite|improve this question
up vote 1 down vote accepted

It looks like a case of confusing word choice. "the next term in another sequence is to multiply the previous term by 3 and then subtract x, where x is an integer" is not very clear, which is not your fault.

Suppose you have a sequence $a_1, a_2, a_3, a_4, ...$. You're given that the rule for each $a_n$ is $a_n = 3a_{n-1} - x$, where $x$ is some integer that's the same for all of them.

Then, given that $a_2 = 7$ and $a_4 = 43$, find $a_1$.

So what you want to do here is find $a_4$ in terms of $a_2$ and solve for $x$.

We have that:

$a_2 = 7 \\ a_3 = 3(7) - x = 21 - x \\ a_4 = 3(21 - x) - x = 63 - 4x$

Since $a_4 = 43$, this means $4x = 20$ and $x = 5$.

Now, work backwards and solve for $a_1$ given $x$:

$a_2 = 3(a_1) - 5\\ 7 = 3(a_1) - 5\\ 3(a_1) = 12\\ a_1 = 4$

which is the answer you want.

share|cite|improve this answer
By the way, if you want to check that you've done it right, here's a different problem for you to solve: Same as above, except the second term is 8 and the fourth term is 56. What is the first term? (It should also be 4.) – Joe Z. Jan 3 '13 at 17:21
Very clear answer which describes both the question and the solution, much appreciated! – PwnageAtPwn Jan 3 '13 at 17:26

Hint: Solve the equation $$3\cdot(7)-x=\frac{43+x}{3}.$$ This gives you the value of $x$. After you find $x$, you can set up the equation $a_2=3\cdot a_1-x$.

share|cite|improve this answer

Hint: Let $y$ be the first element in the series. You are told that $7=3y-x$ from the rule. Then we apply the rule twice to find the fourth term. The third term is $3\cdot 7-x=21-x$. The fourth term is then $43=3(21-x)-x=63-4x$ From this you can find $x$, then substitute into the first to find $y$.

share|cite|improve this answer

Convert what you're told into mathematical language. Say the $n$th term in your sequence is $a_n$. You're given that $a_2=7$ and $a_4=43$. You're also told that $a_n = 3a_{n-1} - x$ for each $n$. Your task is to find $a_1$.

Using this formula you have $a_2 = 3a_1 - x$. You know what $a_2$ is, so as soon as you find $x$, all you have to do is rearrange this and you're done.

How do you find $x$? Well you know

$$a_3 = 3a_2 - x$$


$$a_4 = 3a_3 - x$$

You know $a_4$ and $a_2$, so substitute the first of these equations into the second and solve for $x$.

share|cite|improve this answer
It's 43, not 47. – Joe Z. Jan 3 '13 at 17:16
@JoeZeng: Thanks - fix'd. Dunno how that happened. – Clive Newstead Jan 3 '13 at 17:17

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.